Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

Muscular Strength Assessment - Axtell, Robert (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Exercise Prescription - Older Adults - Axtell, Robert; Robertson, M. I. (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test. - Lunn, William R.; Axtell, Robert S. (Journal of strength and conditioning research, 2021)
https://europepmc.org/article/MED/31453946 ; https://pubmed.ncbi.nlm.nih.gov/31453946/ ; https://dialnet.unirioja.es/servlet/articulo?codigo=8169588
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Discriminative ability of lower limb strength and power measures in lacrosse athletes - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; Maloney, Maggie; Newman, Thomas; Cordone, Jason; O’Grady, Mathew (International Journal of Sports Medicine, 2023)
The objective of this investigation was to compare isokinetic strength, countermovement jump and drop jump variables between high-contributors and low-contributors within NCAA Division I Men’s and Women’s lacrosse athletes. Men’s (N=36) and Women’s (N=30) NCAA Division I lacrosse athletes completed strength testing of the quadriceps and hamstring across three speeds (60°·s−1, 180°·s−1, 300°·s−1), countermovement and drop jumps. To determine the discriminative ability of select lower-limb strength and power characteristics participants were categorized as high-contributors (Males N=18, age=20.3±0.4 yrs, height=183.9±5.5 cm, mass=90.8±5.8 kg; Females N=15, age=20.8±0.8 yrs, height=169.3±6.7 cm, mass=64.1±7.2 kg) or low-contributors (Males N=18, age=19.5±0.2 yrs, height=184.1±5.6 cm; mass=87.9±8.1 kg; Females N=15, age=19.7±0.2 yrs, height=169.8±7.0 cm, mass=62.9±7.7 kg ) based upon the number of games the participants competed in during the regular season. Within the male cohort, moderate significant (p−1 (d=0.69) and peak power in countermovement jump (d=0.68). Within the women’s cohort a large (d=0.87) significant difference (p−1. Hamstring strength and lower-limb power are important strength measures for lacrosse performance and should be prioritized in training prescription for lacrosse athletes.
0 citations (Crossref) [2023-10-31]
Keywords: Key words countermovement jump; dept.hms; drop jump; female athlete; peer-reviewed; performance

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Current activities centered on healthy living and recommendations for the future: A position statement from the HL-PIVOT network - Arena, Ross; Myers, Jonathan; Kaminsky, Leonard A.; Williams, Mark A.; Sabbahi, Ahmad; Popovic, Dejana; Axtell, Robert S.; Faghy, Mark A.; Hills, Andrew P.; Olivares, Silvia Lizett Olivares; Lopez, Mildred; Pronk, Nicolaas P.; et al. (Current Problems in Cardiology, 2021)
We continue to increase our cognizance and recognition of the importance of healthy living (HL) behaviors and HL medicine (HLM) to prevent and treat chronic disease. The continually unfolding events precipitated by the coronavirus disease 2019 (COVID-19) pandemic have further highlighted the importance of HL behaviors, as indicated by the characteristics of those who have been hospitalized and died from this viral infection. There has already been recognition that leading a healthy lifestyle, prior to the COVID-19 pandemic, may have a substantial protective effect in those who become infected with the virus. Now more than ever, HL behaviors and HLM are essential and must be promoted with a renewed vigor across the globe. In response to the rapidly evolving world since the beginning of the COVID-19 pandemic, and the clear need to change lifestyle behaviors to promote human resilience and quality of life, the HL for Pandemic Event Protection (HL-PIVOT) network was established. The 4 major areas of focus for the network are: (1) knowledge discovery and dissemination; (2) education; (3) policy; (4) implementation. This HL-PIVOT network position statement provides a current synopsis of the major focus areas of the network, including leading research in the field of HL behaviors and HLM, examples of best practices in education, policy, and implementation, and recommendations for the future. © 2021 Elsevier Inc.
10 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103372602
Keywords: Biomedical Research; COVID-19; Cardiorespiratory Fitness; Chronic Disease; Diabetes Mellitus; Diet; Exercise; Health Education; Health Policy; Healthy; Healthy Lifestyle; Humans; Implementation Science; Information Dissemination; Obesity; Patient Education as Topic; Quality of Life; Review; Risk Reduction Behavior; SARS-CoV-2; Sedentary Behavior; Smoking Cessation; Type 2; body mass; cardiorespiratory fitness; chronic disease; coronavirus disease 2019; dept.hms; education; epidemiology; exercise; health; health behavior; health care personnel; health care planning; health care policy; health education; health promotion; healthy diet; healthy lifestyle; healthy living medicine; human; information dissemination; knowledge; knowledge discovery; law; lifestyle; medical research; medicine; non insulin dependent diabetes mellitus; nutrition; obesity; pandemic; patient education; peer-reviewed; physical activity; psychological resilience; quality of life; risk reduction; sedentary lifestyle; sleep; smoking cessation; syndemic; unhealthy lifestyle behavior